Pengaruh Media Permainan Ular Tangga Digital Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Pancasila Kelas V di SD IT Al-Furqan Palangka Raya - Maulida, Lutfia; Rahmad, Rahmad; Sulistyowati, Sulistyowati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2025)
This research is motivated by the existence of real problems in the learning process in the Pancasila Education subject, namely student learning outcomes that have not yet reached the KKM. This is due to the minimal use of digital-based learning media. Therefore, the solution that can be done to deal with this problem is to use digital snakes and ladders game media. Given the availability of adequate facilities and infrastructure, it is possible to use this media in schools. The purpose of this study was to determine the applicability of digital snakes and ladders game media, learning outcomes, and the effect of digital snakes and ladders game media on student learning outcomes in the Pancasila Education subject for grade V at SD IT Al-Furqan Palangka Raya. The method used in this study was to use a quantitative one group pretest-posttest design. Data collection techniques consisted of observation, testing, and documentation. Then, the population was grade V students of SD IT Al-Furqan Palangka Raya with a total of 31 students. Sampling using purposive sampling technique, so the sample in this study was grade V Abu Hanifah students of SD IT Al-Furqan Palangka Raya totaling 17 students. The results of the study showed that: (1) in the observation of the application of the learning process using digital snakes and ladders game media, it obtained a value of 95,2% with the category "Very Good"; (2) the learning outcomes of class V Abu Hanifah students in the Pancasila Education subject before being given treatment obtained an average value of 68.97 with the category "Enough". Then, the learning outcomes after being given treatment obtained an average value of 89.78 with the category "Very High"; (3) Based on the results of the Wilcoxon t-test, a significance value of 0.001 <0.05 was obtained so that Ha was accepted. This means that the digital snakes and ladders game media has an effect on the learning outcomes of students in the Pancasila Education subject of class V Abu Hanifah at SD IT Al-Furqan Palangka Raya.